2004
DOI: 10.1039/b314080f
|View full text |Cite
|
Sign up to set email alerts
|

A fast passive and planar liquid sample micromixer

Abstract: A novel microdevice for passively mixing liquid samples based on surface tension and a geometrical mixing chamber is presented. Due to the laminar flow regime on the microscale, mixing becomes difficult if not impossible. We present a micromixer where a constantly changing time dependent flow pattern inside a two sample liquid plug is created as the plug simply passes through the planar mixer chamber. The device requires no actuation during mixing and is fabricated using a single etch process. The effective mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 16 publications
0
54
0
Order By: Relevance
“…While other researches have developed static Y-junction microvalves to catch and hold liquid streams using surface tension against tapered channel walls, samples may only be released when an adjacent fluid stream overcomes surface tension and subsequently combines with the sample. 29,30 Other static resistance features exist for catching samples in microfluidic serial processes using hydrophobic patches, 15 or temperature control methods. 31 However, latches are the most aptly suited alignment mechanism for our application.…”
Section: Microfluidic Latchmentioning
confidence: 99%
“…While other researches have developed static Y-junction microvalves to catch and hold liquid streams using surface tension against tapered channel walls, samples may only be released when an adjacent fluid stream overcomes surface tension and subsequently combines with the sample. 29,30 Other static resistance features exist for catching samples in microfluidic serial processes using hydrophobic patches, 15 or temperature control methods. 31 However, latches are the most aptly suited alignment mechanism for our application.…”
Section: Microfluidic Latchmentioning
confidence: 99%
“…5. Each channel contact point can be designed as a narrow opening that functions as a geometric capillary valve (Melin, 2004) to avoid bubble trapping: if only one side of an opening is wetted, the surface energy prevents the liquid--gas interface to cross the opening. Once both sides of the opening are wetted, flow through the opening is allowed.…”
Section: Verification Of the Assumptions And Approximationsmentioning
confidence: 99%
“…Such designs have been realised in the form of parallel microchannels arranged in an arborescent pattern (Juncker, 2002) or arrays of posts (Gervais, 2011), or meshes (Mirzaei, 2010). Based on a microfluidic design by Melin et al (Melin, 2004), Safavieh et al reported a CP design with varying capillary flow based on a meandering channel design containing geometric capillary valves between the meander arms. Capillary suction when the liquid front is at position x…”
Section: Introductionmentioning
confidence: 99%
“…Serpentine or zigzag shapes are frequently used as microchannels to increase the ratio of the channel surface area to its volume. Based on these basic designs, intersecting channels could be added to split, rearrange, and combine flow streams (He et al, 2001;Melin et al, 2004). Additionally, three-dimensional serpentine structures were developed to promote a chaotic mixing effect (Liu et al, 2000;Vijayendran et al, 2003).…”
Section: Driving and Control Of Fluidsmentioning
confidence: 99%